Left atrial strain predicts the rhythm outcome in patients with persistent atrial fibrillation undergoing left atrial cryoablation during minimally invasive mitral valve repair - Yildirim, Yalin; Yildirim, Sevenai; Petersen, Johannes; Alassar, Yousuf; Sarwari, Harun; Sinning, Christoph; Blankenberg, Stefan; Reichenspurner, Hermann; Pecha, Simon (Frontiers in Cardiovascular Medicine, 2024)
Objectives Patients with atrial fibrillation (AF) have lower left atrial (LA) strain, which is a predictor for LA function. Here, we evaluated the prognostic value of LA strain to predict the rhythm outcome in patients with persistent AF undergoing LA cryoablation concomitant to minimally invasive mitral valve repair. Methods Between 01/2016 and 12/2020, 72 patients with persistent AF underwent LA cryoablation during minimally invasive mitral valve surgery. All patients received a complete LA lesion set and left atrial appendage (LAA) closure with a clip. All patients received preoperative transthoracic echocardiography (TTE) with LA and left ventricular strain measurements. Preoperative LA and LV strain analysis was correlated with postoperative rhythm outcome. Results The mean age of the patients was 66.9 ± 7.2 years, of whom 42 (58%) were male patients. No major ablation-related complications occurred in any of the patients. Successful LAA closure was confirmed by intraoperative echocardiography in all patients. The 1-year survival rate was 97%. Freedom from AF at 12 months was 72% and 68% off antiarrhythmic drugs. Preoperative LA strain values were statistically significantly higher in patients with freedom from AF at 12 months of follow-up (12.7% ± 6.9% vs. 4.9% ± 4.1%, p = 0.006). Preoperative LV strain value was not associated with postoperative rhythm outcome. In multivariate logistic regression analysis, LA strain (p < 0.001) and AF duration (p = 0.017) were predictors for freedom from AF at 12 months of follow-up. Conclusions In our study, LA strain analysis predicted the rhythm outcome in patients with persistent AF undergoing concomitant surgical AF ablation. In the future, LA strain might be a useful tool to guide decision-making on ablation strategies in patients with persistent AF.